Low GAS carriage in school-aged children in western China during the national atypical scarlet fever resurgence: Insights from two cross-sectional studies - Mengyang Guo; Xiangping Hou; Wei Shi; Qian Huang; Wei Gao; Limin Dong; Yun Lai; Siyu Chen; Jianghong Deng; Kaihu Yao (Journal of Global Antimicrobial Resistance, 2025)
Introduction: This study examined group A streptococcus(GAS) carriage, emm types, and antibiotic susceptibility in children (6–13 years) in Aral, China, during the post-COVID-19 scarlet fever resurgence, providing regional insights. Methods: The prevalence of GAS carriage was assessed in 1,835 children aged 6–13 years across two surveys at an Aral school in China during the post-COVID-19 resurgence of scarlet fever. GAS isolates were analyzed for emm types, M1UK lineage, and antimicrobial susceptibility using culture, PCR, sequencing, and automated methods. Results: The first survey (885 children) showed a 1.9% isolation rate, highest in 9-year-olds (4.8%) and slightly higher in boys (2.3% vs. 1.5%, P > 0.05). The second survey (950 children) reported a 3.1% rate, peaking at 10 years (6.7%) and also higher in boys (3.5% vs. 2.6%, P > 0.05). Colonization rates were similar overall (P > 0.05), but increased significantly in children aged ≥10 years (1.1% to 3.3%, P = 0.038). No children tested positive for GAS in both sampling rounds, which meant that the two surveys identified distinct host populations colonized by the bacteria. Emm12 prevalence decreased from 76.5% to 55.2% (P > 0.05), while emm1 increased from 11.8% to 31.0% (P > 0.05), with no M1UK lineage detected. All isolates were sensitive to penicillin, linezolid, vancomycin, and levofloxacin. Among 33 co-resistant isolates, emm12 accounted for 84.8% and emm1 for 15.2%. Conclusion: Despite low GAS carriage rates, variations in age distribution and emm types suggest increased bacterial activity, warranting ongoing monitoring for GAS-related diseases.